Alveolar cyst of the adult: Counterpart of gingival cyst of the adult in edentulous ridge - Schulz, Maykon Kennedy [UNESP]; Teixeira, Lucas Ribeiro; Fernandes, Darcy [UNESP]; Bufalino, Andreia [UNESP]; Leon, Jorge Esquiche (Elsevier, 2018)
A 49-year-old man presenting a nodular swelling on the maxillary alveolar mucosa with 2 months of evolution. An imaginological examination revealed superficial bone resorption. By microscopy, typical features of Gingival cyst of the adult (GCA) were observed. However, in the lesional area there are no teeth and consequently periodontium. Thus, the clinicopathological correlation favored a diagnosis of alveolar cyst of the adult, counterpart of the GCA but on the edentulous maxilla or mandible.
Keywords: Edentulous maxilla; Gingival cyst of the adult; Histopathology; Lateral periodontal cysts; Odontogenic cyst